Protective Effects of Irbesartan, an Angiotensin Receptor Blocker with PPARγ Agonistic Activity, against Estradiol Benzoate-Induced Endometrial Hyperplasia and Atypia in Female Rats via Modulation of TNFα/Survivin Pathway - Mohamed A. Morsy; Wedad M. Abdelraheem; Maram El-Hussieny; Marwa M. M. Refaie (MDPI AG, 2021)
Endometrial hyperplasia (EH) is a common gynecological problem and may progress to carcinoma. Early detection and management of EH are mandatory for the prevention of endometrial cancer. Activation of the renin-angiotensin system and angiotensin II signaling are involved in the progression of precancerous and cancerous lesions. However, no studies have evaluated the role of this system in estradiol benzoate (EB)-induced EH and atypia. Irbesartan (IRB), an angiotensin II receptor blocker with peroxisome proliferator-activated receptor gamma (PPARγ) agonistic activity was administered (30 mg/kg/d) in EB-treated (60 µg/100 g bodyweight, intramuscularly, three times per week) or untreated rats for 4 weeks. Uterine weight changes, malondialdehyde, superoxide dismutase (SOD), tumor necrosis factor-alpha (TNFα), survivin, cleaved caspase 3, interleukin-10 (IL10), and PPARγ were measured in addition to undergoing histopathological examination. Results showed that EB-induced EH and atypia significantly increased the uterine body weight, malondialdehyde, TNFα, and survivin, accompanied with significantly decreased SOD, cleaved caspase 3, IL10, and PPARγ, with typical histopathological changes of EH and atypia. Coadministration of IRB significantly prevented EB-induced biochemical and histopathological changes. The protective effects of IRB may be attributed to its anti-inflammatory and antioxidant properties, reduction of survivin, and increased levels of cleaved caspase 3.